M-LEARNING TEXNOLOGIYASINING QO’LLANILISHI - Davronbek Qodirov Rajabboy oʻgʻli; Toʻliboyeva Umida Gulmirza qizi; Tohirjonova Shahzoda Oybekjon qizi; Tursunboyeva Mahbuba Oʻrazboy qizi (PEDAGOGS, 2024)
Abstract: Modern society is rapidly developing, and the requirements for, professional education are changing accordingly. Nowadays, the term “mobile learning” appears in teaching methods. Mobile education is a new direction of pedagogy and education, learning using mobile technologies that allow organizing the educational process using mobile communication tools. Using mobile devices, students can access learning resources, connect with other users, and create content in and out of the classroom.